Pengaruh Courtesy, Empati Dan Kepuasan Nasabah Terhadap Loyalitas Nasabah BMT Assyafi’iyah Cabang Purbolinggo Lampung Timur - Durotun Nasikah; Suwarto Suwarto (Borobudur Management Review, 2021)
The aim of this research were to determine the effect of courtesy, Empathy, and customer satisfaction on customer loyalty. The quantitative approach is implemented in this research. The method of research surveys on 85 customers is taken by accidental sampling and questionnaire as an instrument of research. Findings signify that: 1) courtesy direct effect positively to customer loyalty, 2) Empathy direct effect positively to customer loyalty, 3) customer satisfaction direct effect positively to customer loyalty, 4) courtesy direct effect positively to customer satisfaction, 5) Empathy direct effect positively to customer satisfaction